Debra Seenoi's Zoom transcript, Kenya, January 26, 2021 (Mobilities and Socialities: COVID-19 in the Drylands of Africa and Beyond, 2021)
To have access to the research data file, please contact: Joana Roque de Pinho: roquedepinho.joana@gmail.com
Keywords: Arid regions; Maasai (African people); Sustainable tourism; Food security; Livestock; Travel; Herders; East Africa; Pastoralist; Mobility; Sociality; COVID-19 Pandemic